Pengaruh Jumlah Komite Audit, Pertumbuhan Perusahaan, dan Audit Report Lag terhadap Opini Audit Going Concern (Studi Empiris pada Perusahaan Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Rusdiyantoro Fadhillah; Wiwit Irawati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The issuance of going-concern audit opinions remains a critical issue for publicly listed companies, particularly in capital-intensive sectors vulnerable to financial instability. This study examines whether the number of audit committee members, company growth, and audit report lag influence the likelihood of receiving a going concern audit opinion, with Debt to Asset Ratio (DAR) included as a control variable. The sample consists of 27 Basic Materials companies listed on the Indonesia Stock Exchange during 2020-2024, resulting in 135 firm year observations selected through purposive sampling. Secondary data were obtained from audited annual financial statements and analyzed using logistic regression with the Generalized Estimating Equation (GEE) approach to accommodate panel data characteristics and heteroskedasticity. The findings indicate that company growth significantly affects the probability of receiving a going-concern audit opinion, while the number of audit committee members, audit report lag, and DAR do not show significant partial effects. However, jointly, all independent variables significantly explain variations in going-concern audit opinions. These results suggest that financial performance remains a primary consideration for auditors, while governance structure and reporting timeliness play a complementary role in the assessment process.